AN ANALYSIS OF THE PROCESS OF TRANSLATING RECOUNT TEXTS BY USING GOOGLE TRANSLATION MACHINE - Ikrimah, Ikrimah; K., Salamah H.; Aslamiyah, Suaibatul; Fauzan, Akhmad (International Journal of Humanity Studies (IJHS), 2024)
The research aims to find out the process of translating recount texts by using Google Translation Machine. This study integrated a qualitative phenomenological approach of a group of 18 tenth-grade students at MA Miftahul Jannah, Palangka Raya. Online questionnaires via Google Forms and unstructured follow-up interviews were employed. The 15-question questionnaire, featuring both open-ended and closed-ended formats, explored aspects ranging from general usage of resources, such as Google Translation Machine, to specific processes in translating recount texts. The result of this research showed the students' process in translation began with comprehensively reading the text to gain full understanding. Following this initial step, they mentally process their translation before writing it down. In the translating phase, Google Translate was an essential tool. Some students used it directly, while others employed it as a guide for their translations. The focus here was on the accurate selection of words, phrases, and sentences. Once the translation was complete, the majority of the students cross-checked their work against the original text to maintain fidelity. However, a small number skipped this critical revision step. This highlighted the necessity of reinforcing the importance of evaluation and revision stages in the translation process.